Effects of red dragon fruit (Hylocereus polyrhizus) peel on low-density lipoprotein levels in menopause wistar rats - Dyta Putri Aryo; I Wayan Sugiritama; I Gusti Nyoman Sri Wiryawan; I Gusti Ayu Dewi Ratnayanti (Bali Anatomy Journal, 2020)
Background: Estrogen has major role to control LDL levels in woman’s body, therefore if a woman experienced hypoestrogen condition usually during menopause phase, there is an increase of the LDL levels. Anthocyanin has similar structure with isoflavones, which have been widely studied and proven to be estrogenic. One of the food ingredients that is rich in anthocyanin is the peel of red dragon fruit (Hylocereus polyrhizus), so it is hoped that this red dragon fruit peels can be a source of phytoestrogens that can play a role in improving LDL levels in menopausal women. Aim: To determine the effect of red dragon fruit peel (Hylocereus polyrhizus) on Low Density Lipoprotein levels in menopause wistar rats. Method: This study was a purely experimental study with a randomized post-test only control group design with a sample of 27 female wistar rats that had fulfilled the inclusion and exclusion criteria. The study sample was divided into 3 (three) groups with each group consisting of 9 female wistar rats, namely the control group (P0), the ethanol extract of red dragon fruit peels at a dose of 60mg / 200grBB group (P1), and dose 90mg / 200grBB group (P2).Result: There was a significant difference between P0 and P1 so that between P0 and P2, meanwhile comparison between P1 and P2 showed only slight difference. Conclusion: The red dragon peel extract can control LDL levels, therefore it is possible to be a substitute of estrogen endogen in menopausal women.